THU0296 Influenza and Pneumococcal Vaccination in Patients on Biotherapies. A Report on 594 Patients from Four Hospitals. (10th June 2014) - Brocq, O.; Berthier, F.; Albert-Sabonnadiere, C.; Bolla, G.; Millasseau, E.; Destombe, C.; Azulay, J.; Asquier, C.; Acquacalda, E.; Florent, A.; Le Seaux, S.; Euller-Ziegler, L.
Abstract : Objectives: To evaluate pneumococcal (PV) and influenza (IV) vaccination status in patients (pts) on biotherapies by researching influencing factors. Methods: Pts on biotherapies seen between February and July 2013 were questioned about PV and IV status. Variables analysed: age, sex, disease, treatment, immunisation status, reason for non-vaccination and history of pulmonary infection on biotherapy. Percentage comparisons were performed using chi-square and McNemar's tests. Results: 594 pts were analysed (406 F + 188 M): 307 rheumatoid arthritis (RA) (51 M +256 F, mean age 59 years); 277 spondyloarthritis (SpA) (135 M +142 F, mean age 48 years); and 10 other diseases. In the RA group, 189 pts were treated with anti-TNFs: 115 with etanercept (Etn); 37 with adalimumab (Ada); 19 with infliximab (Inf); 13 with certolizumab (Cer); and 5 with golimumab (Gol). 118 other pts were treated with another biotherapy, including 42 with rituximab (Rtx); 38 with tocilizumab (To); 24 with abatacept (Aba); and 14 with anakinra (Ana);151 pts had at least 2 biotherapies. One DMARD was combined in 60% and cortisone in 35%. In the SpA group, 271 were treated with anti-TNFs (Ada 121, Etn 85, Inf 46, Gol 14, Cer 5) and 6 with other biotherapies, 86 pts had at least 2 biotherapies. One DMARD was combined in 28% and cortisone in 5%. The 2012-2013 winter IV (recommended for 37% by the general practitioner [GP]; 45% for RA and 28% for SpA), and in 63% after age 65, and in 79% by the rheumatologist (including 82% for RA and 75% for SpA, and in 93% after age 65) was given to 260 pts (43.77%; including 44% for RA and 43% for SpA and in 62% of pts >65 years). Pts having refused were 47%, (55% were RA and 39% were SpA), generally because of fear (45% RA and 32% SpA). PV over the last 5 years (recommended in 14% by the GP, including 16% for RA and 12% for SpA, and in 24% after age 65, and in 78% by the rheumatologist in RA and SpA, and in 86% after age 65) had been done for 370 pts (62.29%; including 60% in RA and 65% in SpA, and in 70% over age 65). Pts having refused were 25% (31% RA and 17% SpA). In total, 37% had two vaccinations (53% after age 65): 33% one of two; 30% neither of the two. 67 pts (48 RA) had an infection (11%), including 20 hospitalisations. Variables selected for a better vaccination: a prior IV; the recommendation by the GP and the rheumatologist (p<0.001); age >65 years (IV p<0.001, PV p=0.02). The other parameters were not influencing (type and number of biotherapies, DMARDs, cortisone, disease). Infections were not lower in those vaccinated compared to those non-vaccinated (number of pts too low). The PV was up-to-date more frequently than the IV (p<0.001) in the two diseases. Fear of side effects was one of the causes of non-vaccination. Conclusions: The rate of IV was 44% compared to 62% for PV. Age influences the vaccination status, as well as the information given to the patient. This should be repeated with pts and physicians in order to improve protection. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1935